Oral history interview with Robert "Doo" Hickman, April 20, 2001 - Hickman, Robert "Doo" (Valdosta State University Archives and Special Collections, 2001)
Oral history interview with Robert "Doo" Hickman, April 20, 2001. Gainesville (Ga.). Fieldworker: Chip Zoller. Audio file digitized from cassette tape. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. Topics include Native American music and traditional instruments.
1 electronic record(s) and derivatives. 18 audio files (wav, mp3) 1386242524 bytes. 00:58:32. 2 PDF documents (6 scans, jp2). 2.79 GB (3,002,370,540 bytes)
Keywords: Georgia; Oral histories; Sound recordings; Gainesville (Ga.); Muscogee (Creek) Nation; Native American flute